Regional anaesthesia quality indicators for adult patients undergoing non‐cardiac surgery: a systematic review. (10th January 2021) - Hamilton, G. M.; MacMillan, Y.; Benson, P.; Memtsoudis, S.; McCartney, C. J. L.
Summary: Improvement in healthcare delivery depends on the ability to measure outcomes that can direct changes in the system. An overview of quality indicators within the field of regional anaesthesia is lacking. This systematic review aims to synthesise available quality indicators, as per the Donabedian framework, and provide a concise overview of evidence‐based quality indicators within regional anaesthesia. A systematic literature search was conducted using the databases MEDLINE, Embase, CINAHL and Cochrane from 2003 to present, and a prespecified search of regional anaesthesia society websites and healthcare quality agencies. The quality indicators relevant to regional anaesthesia were subdivided into peri‐operative structure, process and outcome indicators as per the Donabedian framework. The methodological quality of the indicators was determined as per the Oxford Centre for Evidence‐Based Medicine's framework. Twenty manuscripts met our inclusion criteria and, in total, 68 unique quality indicators were identified. There were 4 (6%) structure, 12 (18%) process and 52 (76%) outcome indicators. Most of the indicators were related to the safety (57%) and effectiveness (19%) of regional anaesthesia and were general in nature (60%). In addition, most indicators (84%) were based on low levels of evidence. Our study is an important first step towards describing quality indicators for the provision of regional anaesthesia. Future research should focus on the development of structure and process quality indicators and improving the methodological quality and usability of these indicators.